PEMBUATAN GLUKOSA CAIR DARI SINGKONG JENIS BAGOR DAN BAROKAH DENGAN METODE HIDROLISIS ENZIMATIS MENGGUNAKAN ENZIM AMILASE - Yunita Khilyatun Nisak; M. Nurul Huda (Ekliptika, 2023)
Sugar is one of the basic needs of society, which is generally used as a natural sweetener, sugar consists of 2 types, namely crystal and liquid. Liquid sugar can be produced from various sources of starch such as potatoes, corn and cassava. The raw materials used for this study were cassava types of barokah and bagor. Cassava (Manihot esculenta) is a staple food for the Indonesian population. Cassava is known for its high starch content, which is as much as 85%, the high starch content of cassava can be used as an ingredient for the manufacture of liquid sugar. Cassava starch can be turned into liquid sugar through an enzymatic hydrolysis process using the amylase enzyme with an enzyme concentration of 0.1, 0.2, 0.3% This study aims to determine the type of cassava which produces a lot of liquid glucose and to determine the effect of several uses of amylase enzyme concentrations used to produce liquid glucose in cassava. This research was carried out using a randomized block design (RBD) method using 2 factors, namely factor A cassava variety, factor B amylase enzyme concentration 0.1%, 0.2%, 0.3% were repeated 3 times each, the results of the starch analysis showed positive results containing starch marked with a change in dark blue/purple color, the highest yield results were on bagor cassava at a concentration of 0.3% the yield was 62.83 ± 1.49a, the sugar content test was 27.00 ± 6.24a.